2021
DOI: 10.3390/ijms22115934
|View full text |Cite
|
Sign up to set email alerts
|

(5′S) 5′,8-cyclo-2′-deoxyadenosine Cannot Stop BER. Clustered DNA Lesion Studies

Abstract: As a result of external and endocellular physical-chemical factors, every day approximately ~105 DNA lesions might be formed in each human cell. During evolution, living organisms have developed numerous repair systems, of which Base Excision Repair (BER) is the most common. 5′,8-cyclo-2′-deoxyadenosine (cdA) is a tandem lesion that is removed by the Nucleotide Excision Repair (NER) mechanism. Previously, it was assumed that BER machinery was not able to remove (5′S)cdA from the genome. In this study; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 65 publications
3
11
0
Order By: Relevance
“…The results are presented in the Supplementary Materials, i.e., the found and calculated masses are reported in Table S1 and the mass spectra in Figure S2. The substrate oligos were stable in the conditions of the experiment as shown in previous studies: melting temperatures were above 70 • C [42] and matrix strands (native and containing cdPu) were not susceptible to the action of repair enzymes present in NE [2,10,40].…”
Section: The Substrate Oligonucleotidessupporting
confidence: 67%
See 3 more Smart Citations
“…The results are presented in the Supplementary Materials, i.e., the found and calculated masses are reported in Table S1 and the mass spectra in Figure S2. The substrate oligos were stable in the conditions of the experiment as shown in previous studies: melting temperatures were above 70 • C [42] and matrix strands (native and containing cdPu) were not susceptible to the action of repair enzymes present in NE [2,10,40].…”
Section: The Substrate Oligonucleotidessupporting
confidence: 67%
“…The two cell lines were used-BJ (human skin fibroblasts) and XPC (skin fibroblasts from Xeroderma Pigmentosum patient, complementation group C, see Section 2.5). The experimental model was, as previously described, synthetic double-stranded oligonucleotides containing dU (AP site precursor) and 5 ,8-cyclo-2deoxyadenosine (cdA) (5 S and 5 R isomer) on the same (ssCDL) or the opposite strand (dsCDL) (Table 1) [10,40,42]. Each step of the substrate ds-oligonucleotide preparation was verified, and the results are presented in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The BER process is impaired when repair enzymes cannot form complexes with DNA due to structural changes in the double helix, such as those resulting from cdPus occurrence [10]. Interestingly, a recent study showed that BER can remove ScdA from the genome, but the lesion location was crucial for proper enzymes' action [26]. Even though the mitochondrial BER (mtBER) is the best-characterized repair system in mitochondria, many questions remain to be answered.…”
Section: Introductionmentioning
confidence: 99%